Fall-cone strength testing of municipal sludges and residues. Issue 1 (20th June 2016) - O'Kelly, Brendan C
Abstract : This state-of-the-art paper discusses determinations of remoulded undrained shear strength ( s u ) for municipal sludge and residue materials by the fall-cone approach, used increasingly for this purpose in practice. The strength mobilised by a falling cone as it penetrates into a soil test-specimen is related to its 'static' strength s u (used in design for most conventional loading cases) through a rate dependence parameter. From a review of the literature and analyses of existing and new experimental data, compared with inorganic soils, these highly organic soils are found to exhibit significantly greater strain-rate dependence for strength, which reduces correspondingly the value of Hansbo's cone factor K . Hence, in the absence of reported experimental K values for different organic soils, use of inorganic soil K values in strength calculations can often result in significant overestimations of undrained strength. Recommendations are made regarding the cone characteristics more suitable for such testing and experimental approaches useful for determining related K values. Other influencing factors, including the fibrous nature of some organic soils and cone roughness (adhesion), are discussed. The paper concludes by presenting semi-logarithmic and power model formulations for s u determinations from measured water contents as interim (alternative) methods until the mentioned issues are satisfactorily resolved.